2020
DOI: 10.3389/fmicb.2020.02096
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gut Microbiota Diversity and Predicted Functions Between Healthy and Diseased Captive Rana dybowskii

Abstract: The gut microbiota plays a key role in host health, and disruptions to gut bacterial homeostasis can cause disease. However, the effect of disease on gut microbiota assembly remains unclear and gut microbiota-based predictions of health status is a promising yet poorly established field. Using Illumina high-throughput sequencing technology, we compared the gut microbiota between healthy (HA and HB) and diarrhoeic (DS) Rana dybowskii groups and analyzed the functional profiles through a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…Moreover, captive lemurs from the DLC and NCZ in the U.S. had some of the most diverse gut consortia, equaling the greatest diversity seen in wild lemurs (e.g., in BEZ lemurs). These results add to the mounting evidence 61,82,83 that alpha diversity alone, without the context of host ecology and other microbiome data, should not be used to extrapolate about the health state of gut consortia or the host’s environment.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, captive lemurs from the DLC and NCZ in the U.S. had some of the most diverse gut consortia, equaling the greatest diversity seen in wild lemurs (e.g., in BEZ lemurs). These results add to the mounting evidence 61,82,83 that alpha diversity alone, without the context of host ecology and other microbiome data, should not be used to extrapolate about the health state of gut consortia or the host’s environment.…”
Section: Discussionmentioning
confidence: 60%
“…6). However, studies have shown remarkable differences in the gut microbiota between healthy and ill animals (e.g., R. dybowskii), and a signi cant positive correlation exists between the community and functional composition, indicating that the composition of the gut bacterial community in diseased animals has lower functional redundancy [14,18]. The degree of dysbiosis caused by antibiotics and diarrhoea in the gut microbiota may differ.…”
Section: The Effect Of An Antimicrobial Bath On the Function Of The Gmentioning
confidence: 99%
“…Diarrhoea is also probably followed by the disappearance of functional redundancy, which may be related to the severity and progression of dysbiosis [17]. The functional redundancy of the same species may differ among developing statuses [18]. For example, gut redundancy in infants may largely surpass that in adults [17].…”
Section: The Effect Of An Antimicrobial Bath On the Function Of The Gmentioning
confidence: 99%
See 2 more Smart Citations